The Influence of Regional Wealth, Regional Expenditure and General Allocation Funds on Regional Government Performance - Wa Ode Aprisilia Zahratun Azis; Mulyati Akib (PT. Banjarese Pacific Indonesia, 2025)
This study aims to analyze the effect of regional wealth, regional expenditure, and General Allocation Fund (DAU) on local government performance in Indonesia. Local government performance is strongly influenced by how these three factors are managed and optimized. Well-managed local wealth can increase regional fiscal capacity and reduce dependence on funding from the central government. Effective and efficient local expenditure plays a role in providing quality public services, while DAU makes an important contribution to regions with limited fiscal capacity. The method used in this research is a literature study by analyzing related literature, including scientific articles, government reports, and previous research. The results show that the interaction between the three factors has a significant impact on local government performance, which is reflected in development achievements and improvements in people's quality of life. Recommendations from this study include the need for more efficient management of local wealth, more focused allocation of local expenditure to priority sectors, and reduced dependence on DAU by increasing local own-source revenue (PAD). This study also suggests further research to explore the impact of DAU management on regional fiscal resilience.